Microplastics contamination along the coastal waters of NW Portugal. (September 2020) - Rodrigues, S.M.; Almeida, C. Marisa R.; Ramos, S.
Abstract: To evaluate the current microplastics (MPs) contamination on the NW coast of Portugal, opportunistic samples from coastal areas with different levels of anthropogenic impacts were analyzed. Water samples were collected from a coastal marine protected area, an urban estuary, a submarine wreck, and a recreational marina. An optimized protocol for the quantification of MPs, followed by visual identification and FTIR spectroscopy analysis was used to characterize MPs (polymer, type, size, color). MPs were found in all the case studies. A total of 2456 ​MPs particles were identified and classified as fibers (39%), film (39%), and fragments (22%). Up to 54% of MPs had a size range between 1 and 3 ​mm. Transparent was the dominant color (56%), followed by white (19%). Polyethylene and polypropylene were the main MPs polymers detected. Higher MPs concentration were found in areas associated with high intense fishing and shipping activities. This study showed that different types of MPs were present in all the aquatic environments surveyed, mainly in areas with more anthropogenic activities, emphasizing the need for measures to properly manage plastic litter and mitigate marine plastic pollution. Graphical abstract: Image 1 Highlights: Microplastics were found in all the case studies. Different microplastics concentration, type, size, and color were found in the four case studies. Microplastics concentration ranged from 0.015 to 4028 ​MPs particles/m 3 . Small and transparent fibers were the most abundant type of MPs found, and only secondary microplastics were observed. PE, PP, PA, PET, and nylon were the polymers detected.